2020
DOI: 10.1038/s41598-020-78546-1
|View full text |Cite
|
Sign up to set email alerts
|

Developmental asymmetries in learning to adjust to cooperative and uncooperative environments

Abstract: Learning to successfully navigate social environments is a critical developmental goal, predictive of long-term wellbeing. However, little is known about how people learn to adjust to different social environments, and how this behaviour emerges across development. Here, we use a series of economic games to assess how children, adolescents, and young adults learn to adjust to social environments that differ in their level of cooperation (i.e., trust and coordination). Our results show an asymmetric development… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 68 publications
1
25
1
Order By: Relevance
“…First, prosocial learning was restricted to unknown others and should be extended in future research to other beneficiaries. Previous studies have shown that prosocial behaviors and their neural correlates in adolescence strongly depend on the beneficiary (e.g., (Brandner et al, 2020;Schreuders et al, 2018;Westhoff et al, 2020). Whether such differences between beneficiaries are also visible in prosocial learning and the concurrent neural tracking of PEs, is an interesting question for future studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…First, prosocial learning was restricted to unknown others and should be extended in future research to other beneficiaries. Previous studies have shown that prosocial behaviors and their neural correlates in adolescence strongly depend on the beneficiary (e.g., (Brandner et al, 2020;Schreuders et al, 2018;Westhoff et al, 2020). Whether such differences between beneficiaries are also visible in prosocial learning and the concurrent neural tracking of PEs, is an interesting question for future studies.…”
Section: Discussionmentioning
confidence: 94%
“…Possibly, age-related differences in brain activity during prosocial PE tracking are explained by other mechanisms. For instance, although there was no reciprocity or competition, participants may have been influenced by social inequality preferences, such as a dislike to getting more (i.e., advantageous inequality aversion), or less (i.e., disadvantageous inequality aversion) than the other participant (Dawes et al, 2007;Fehr & Schmidt, 1999;Meuwese et al, 2015;Westhoff et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Also, age-related differences in brain activity during prosocial PE tracking may be explained by other social cognitive mechanisms than empathy. For instance, although there was no reciprocity or competition, participants may have been influenced by social inequality preferences, such as disliking to getting more (i.e., advantageous inequality aversion), or less (i.e., disadvantageous inequality aversion) than the other participant ( Dawes et al, 2007 , Fehr and Schmidt, 1999 , Meuwese et al, 2015 , Westhoff et al, 2020 ). Future studies could more explicitly assess several social-cognitive skills, strategies, and motivations along with a prosocial learning task to examine what behavioral mechanisms rely most on adolescents’ prosocial learning.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it would be interesting if future research would extend the prosocial learning task to other beneficiaries. Previous studies have shown that prosocial behaviors and their neural correlates in adolescence strongly depend on the beneficiary (e.g., Brandner et al, 2020 , Schreuders et al, 2018 , van de Groep et al, 2020 , Westhoff et al, 2020 ). Future studies should further examine whether such differences between beneficiaries are also visible in prosocial learning and whether this affects the concurrent neural tracking of PEs.…”
Section: Discussionmentioning
confidence: 99%
“…showing longitudinal relation between economic inequality and individuals' prosocial behavior from 1973 to 2012. However, previous researches' models had their limitations considering the interest variables (e.g., prosocial behavior) were viewed as static and non-developmental throughout adolescence, which is a particular period of rapid change in prosocial behaviors (Westhoff et al, 2020). With the development of autonomy and identity exploration, adolescents are more likely to engage in several prosocial behaviors, such as volunteering and donating (McGinley et al, 2021).…”
Section: Developmental Processes Of Prosocial Behaviormentioning
confidence: 99%